Dysfunction in differential reward-punishment responsiveness in conduct disorder relates to severity of callous-unemotional traits but not irritability. Issue 5 (1st April 2023) - Zhang, Ru; Aloi, Joseph; Bajaj, Sahil; Bashford-Largo, Johannah; Lukoff, Jennie; Schwartz, Amanda; Elowsky, Jamie; Dobbertin, Matthew; Blair, Karina S.; Blair, R. James R.
Abstract: Background: Conduct disorder (CD) has been associated with dysfunction in reinforcement-based decision-making. Two forms of affective traits that reflect the components of CD severity are callous-unemotional (CU; reduced guilt/empathy) traits and irritability. The form of the reinforcement-based decision-making dysfunction with respect to CD and CU traits remains debated and has not been examined with respect to irritability in cases with CD. The goals of the current study were to determine the extent of dysfunction in differential (reward v . punishment) responsiveness in CD, and CU traits and irritability in participants with CD. Methods: The study involved 178 adolescents [typically developing (TD; N = 77) and cases with CD ( N = 101)]. Participants were scanned with fMRI during a passive avoidance task that required participants to learn to respond to (i.e. approach) stimuli that engender reward and refrain from responding to (i.e. passively avoid) stimuli that engender punishment. Results: Adolescents with CD showed reduced differential reward-punishment responsiveness within the striatum relative to TD adolescents. CU traits, but not irritability, were associated with reduced differential reward-punishment responsiveness within the striatum, rostromedial, and lateral frontal cortices. Conclusions: The results suggest CD is associated with reduced differential reward-punishment responsiveness and the extent of this dysfunction in participants with CD is associated with the severity of CU traits but not irritability.